Anatomy eaudiobook A love story. - Schwartz, Dana (The Anatomy Duology, 2022)
This audiobook includes a bonus interview with the author. *INSTANT #1 NEW YORK TIMES BESTSELLER* *INSTANT #1 INDIE BESTSELLER* *INSTANT USA TODAY BESTSELLER* *A REESE'S YA BOOK CLUB PICK* Dana Schwartz's Anatomy: A Love Story is a gothic tale full of mystery and romance. Hazel Sinnett is a lady who wants to be a surgeon more than she wants to marry. Jack Currer is a resurrection man who's just trying to survive in a city where it's too easy to die. When the two of them have a chance encounter outside the Edinburgh Anatomist's Society, Hazel thinks nothing of it at first. But after she gets kicked out of renowned surgeon Dr. Beecham's lectures for being the wrong gender, she realizes that her new acquaintance might be more helpful than she first thought. Because Hazel has made a deal with Dr. Beecham: if she can pass the medical examination on her own, Beecham will allow her to continue her medical career. Without official lessons, though, Hazel will need more than just her books—she'll need corpses to study. Lucky that she's made the acquaintance of someone who digs them up for a living, then. But Jack has his own problems: strange men have been seen skulking around cemeteries, his friends are disappearing off the streets, and the dreaded Roman Fever, which wiped out thousands a few years ago, is back with a vengeance. Nobody important cares—until Hazel. Now, Hazel and Jack must work together to uncover the secrets buried not just in unmarked graves, but in the very heart of Edinburgh society.